All-Cause and Cause-Specific Mortality in Parents After the Death of a Child in Taiwan: A Population-Based Cohort Study. Issue 3 (26th April 2023) - Chen, Ying-Yeh; Gunnell, David; Wu, Chia-Kai; Hu, Ya-Hui; Lee, Pei-Chen
ABSTRACT: Objective: Research from Western countries suggests that there is an increase in mortality in parents bereaved by the death of a child. Few studies have investigated this issue in a non-Western context. We explored the impact of the death of a child on parental mortality in Taiwan. Method: By linking population-based national registers, we followed the 2004–2014 birth cohort ( N = 2, 083, 972) up until 2016. A total of 11, 755 child deaths were identified. For each deceased child, four living children matched on age and sex were randomly selected; their parents were the comparison group. We used Cox proportional hazards regression models to compare the mortality risk of bereaved parents with the comparison group up until 2017. Results: Overall mortality risk was increased in parents who experienced the death of a child; the risk was higher in bereaved mothers (adjusted hazard ratio = 4.91, 95% confidence interval = 3.96–6.09) than fathers (adjusted hazard ratio = 1.82, 95% confidence interval = 1.55–2.13). The risk did not differ according to the sex of the child, but parents whose children died of unexpected causes (i.e., suicide/accidents/violence) were at greater risk than those dying of other causes. Risk was higher when the child was older than 1 year at the time of death than for deaths before age 1 year. Conclusions: Parents who lost a child were at increased mortality risk in this East Asian population. Special attention should be paid to the health of bereaved parents and explore the pathways leading to their risk.